INFORMATION ON THE ECOLOGICAL SITUATION OF THE SAMARKAND REGION IN THE SECOND HALF OF THE XIX - BEGINNING OF THE XX CENTURY IN THE WORK OF I.I. GEYER “TURKESTAN” - Турсунов Р. Н., (TARIXIY TADQIQOTLAR, 2025)
The article, based on the work of the vice-governor of the Syrdarya region, Russian ethnographer I. Geyer, studies the geographical location and environmental condition of Samarkand, one of the regions of Turkestan in the second half of the XIX – beginning of the XX centuries. This work serves as an important source for explaining the history of the Turkestan region, and in particular the environment and environmental situation of the Samarkand region.